2011
DOI: 10.1021/ol103108z
|View full text |Cite
|
Sign up to set email alerts
|

Facile Syntheses of Novel Benzo- 1,3-dioxolo-, Benzothiazolo-, Pyrido-, and Quinolino-fused 5H-Benzo[d]-pyrazolo[5,1-b][1,3]-oxazines and 1H-Pyrazoles

Abstract: A number of novel benzo-1,3-dioxolo-, benzothiazolo-, pyrido-, and quinolino-fused 5H-benzo[d]pyrazolo[5,1-b][1,3]-oxazines and 1H-pyrazoles were synthesized utilizing an easy and effective N,N-bond forming heterocyclization reaction. In so doing, the substrate scope of this heterocyclization reaction, which starts with o-nitroheterocyclic aldehydes, was expanded to provide several unique heterocyclic compounds for biological screening. This work further demonstrates the versatility of this simple, base-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…4b,c As depicted in Scheme 2, we propose that o -nitrobenzylamine 7 delivers hemiaminal nitroso intermediate 8 under basic conditions and subsequent loss of water renders o -nitrosobenzylidine imine 9 . This o -nitrosobenzylidine imine is an important intermediate that engages two possible pathways to the 2 H -indazole product.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…4b,c As depicted in Scheme 2, we propose that o -nitrobenzylamine 7 delivers hemiaminal nitroso intermediate 8 under basic conditions and subsequent loss of water renders o -nitrosobenzylidine imine 9 . This o -nitrosobenzylidine imine is an important intermediate that engages two possible pathways to the 2 H -indazole product.…”
mentioning
confidence: 97%
“…3 In recent years, we have reported the syntheses of a number of pyrazolo-based heterocycles ( 1 ), 2 H -indazoles ( 2 ) and, subsequently, 1 H -indazolones ( 3a/b ) that were obtained via the Davis-Beirut reaction (Figure 1). 4 We previously suggested that o -nitrosobenzylidine was an important intermediate in this chemistry. As part of our ongoing interest in the development of the Davis-Beirut reaction, we report here both acid and base-catalyzed examples that provide mechanistic insight into the reactions shown in Scheme 1.…”
mentioning
confidence: 99%
“…The chemistry of [1,3] oxazines has long kept a special place among N , O ‐heterocycles . Subunits of those, fused [1,3] oxazines with a bridgehead nitrogen atom and susceptible to biological and medicinal properties, are of interest to chemists .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the regioselective synthesis of pyrazoles from propargyl alcohols with tosylhydrazine via the corresponding hydrazides, which were isolated by our original procedure . Hydrazones have been reported to be a good tool for the synthesis of pyrazoles via intra and intermolecular cyclization reactions with alkynes,, cyclobutanones, and other substituted pyrazoles . However, the corresponding hydrazides are much more rare than the corresponding hydrazones , .…”
Section: Introductionmentioning
confidence: 99%